Phytochemical Analysis and Antibacterial Activity of Seed Extracts of Macrotyloma Uniflorum (Horse Gram) - P, Parvathiraj; M.R, Sudhakaran; G, Athinarayanan; K.R, Narayanan (The Asia Journal of Applied Microbiology, 2015)
The present study deals with preliminary phytochemical screening of seed extracts of Macrotyloma uniflorum (horse gram) and its antimicrobial activity against human bacterial pathogens. Aqueous and alcoholic extracts of Seeds of horse gram were evaluated for antibacterial using well diffusion method against some human bacterial pathogens. Phytochemical studies revealed the presence of carbohydrate, steroid, tannins, phenol, protein and amino acid, and absence of alkaloids, glycosides, flavonoids and saponins. Antibacterial activity was tested against 9 human bacterial pathogens using alcoholic and aqueous extract. On comparing the antibacterial activity by alcoholic and aqueous extracts, they showed a moderate to high activity against 9 human pathogens. On considering the rate of antimicrobial activity against pathogens, alcoholic extract showed a better result in controlling the growth of bacteria than that of aqueous extract.